Differential Expression of Antimicrobial Peptides in Streptococcus pneumoniae Keratitis and STAT3-Dependent Expression of LL-37 by Streptococcus pneumoniae in Human Corneal Epithelial Cells - Prerana Sharma; Natalia Sharma; Priyasha Mishra; Joveeta Joseph; Dilip K. Mishra; Prashant Garg; Sanhita Roy (Pathogens, 2019)
Streptococcus pneumoniae is the leading cause of bacterial keratitis in the developing world with a growing trend of acquiring resistance against various antibiotics. In the current study, we determined the expression of different antimicrobial peptides (AMPs) in response to S. pneumoniae in patients, as well as in primary and immortalized human corneal epithelial cells. We further focused on LL-37 and determined its expression in human cornea infected with S. pneumoniae and studied the killing ability of LL-37 against S. pneumoniae. The expression of AMPs was determined by quantitative PCR and the phosphorylation of signaling proteins was evaluated by immunoblot analysis. LL-37 expression was also determined by immunofluorescence and Western blot method and the killing ability of LL-37 against S. pneumoniae was determined by colony-forming units. Differential expression of antimicrobial peptides was observed in patients with S. pneumoniae keratitis. Although S. pneumoniae induced expression of the AMPs in human corneal epithelial cells (HCEC), it did not induce AMP expression in U937, a human monocyte cell line. S. pneumoniae also caused activation of nuclear factor kappa-light-chain enhancer of activated B cells (NF-κB)and mitogen activated protein kinase (MAPK) pathways in corneal epithelial cells. LL-37 was found to be effective against both laboratory and clinical strains of S. pneumoniae. LL-37 induction by S. pneumoniae in human corneal epithelial cells was mediated by signal transducer and activator of transcription 3 (STAT3) activation, and inhibition of STAT3 activation significantly reduced LL-37 expression. Our study determines an extensive profile of AMPs expressed in the human cornea during S. pneumoniae infection, and suggests the potential of LL-37 to be developed as an alternative therapeutic intervention to fight increasing antibiotic resistance among bacteria.